Voltage/Calcium Uncoupling Underlies Sustained Torsade de Pointes Ventricular Tachyarrhythmia in an Experimental Model of Long QT Syndrome - Himel, Herman D.; Cupelli, Michael; Boutjdir, Mohamed; El-Sherif, Nabil (Frontiers in Physiology, 2021)
BACKGROUND: Clinical experience showed that the majority of Torsade de Pointes (TdP) ventricular tachyarrhythmia (VT) in patients with long QT syndrome (LQTS) are self-terminating (ST), but the few that are non self-terminating (NST) are potentially fatal. A paramount issue in clinical arrhythmology is to understand the electrophysiological mechanism of ST versus NST TdP VT. METHODS: We investigated the electrophysiological mechanism of ST versus NST TdP VT in the guinea pig Anthopleurin-A experimental model of LQTS, a close surrogate model of congenital LQT3. We utilized simultaneous optical recordings of membrane voltage (Vm) and intracellular calcium (Cai) and a robust analytical method based on spatiotemporal entropy difference (Ed) to investigate the hypothesis that early Vm/Cai uncoupling during TdP VT can play a primary role in perpetuation of VT episodes. RESULTS: We analyzed a total of 35 episodes of TdP VT from 14 guinea pig surrogate models of LQTS, including 23 ST and 12 NST VTs. Ed values for NST VT were significantly higher than Ed values for ST VT. Analysis of wave front topology during the early phase of ST VT showed the Cai wave front following closely Vm wave front consistent with a lower degree of Ed. In contrast, NST VT was associated with uncoupling of Vm/Cai wave fronts during the first 2 or 3 cycles of VT associated with early wave break propagation pattern. CONCLUSIONS: Utilizing a robust analytical method we showed that, in comparison to ST TdP VT, NST VT was consistently predated by early uncoupling of Vm/Cai that destabilized wave front propagation and can explain a sustained complex reentrant excitation pattern.